The Effect of Debt-to-Equity Ratio (DER) and Inflation on Profit Growth of Building Construction Companies Listed on the Indonesia Stock Exchange in 2020 - Marnilin, Feni; Irawan, Rahmat; Widjaja, Ichwan Rahmanu (Journal of Social Science and Business Studies, 2024)
Investors require information about the company's profit growth to make informed investment decisions. The company's performance can predict profit growth. This study aims to determine the effect of profitability as measured by the debt-to-equity ratio (DER) and inflation on profit growth in building construction companies listed on the Indonesia Stock Exchange in 2020, partially and simultaneously. This study employed the purposive sampling method to select a sample of 12 building construction companies' annual financial reports from the IDX in 2020. The analysis revealed that the debt-to-equity ratio (DER) significantly and negatively impacted profit growth, while inflation had no effect on it. Simultaneously, the debt-to-equity ratio (DER) and inflation had a significant effect on profit growth. Based on the analyzed results, the management of the company should lessen its reliance on debt sources for operational funds, enhance the efficiency of its own capital sources, and ensure fund transparency to uphold investor confidence and boost future profit growth. The composition of the company's total debt, which includes both short-term and long-term debt, should be carefully considered by management in relation to its total equity. The results of this study indicate that a partially debt-to-equity ratio (DER) has a negative and significant effect on profit growth, and when inflation increases, there will be a decrease in profit growth.